2022
DOI: 10.1093/hr/uhac144
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced volatile emissions and anti-herbivore functions mediated by the synergism between jasmonic acid and salicylic acid pathways in tea plants

Abstract: The interaction between jasmonic acid (JA) and salicylic acid (SA) pathways, which affects plant stress resistance, is mainly considered to be antagonistic. Using an established theoretical model, we investigated how tea plant (Camellia sinensis) volatiles induced by exogenous elicitors of JA and SA pathways are affected by the sequence of the elicitor application, the elicitor identity, and the applied concentrations. We also examined the effects of the volatiles mediated by the JA–SA synergistic interaction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…In addition, several studies have shown that external application of JA can affect terpenoid synthesis efficiency (Ayala-Zavala et al, 2005;Kim et al, 2006). Similarly, the release of volatile terpenoids was significantly increased by external application of JAs to tea leaves (Jiao et al, 2022). However, this causal linkage between JA and terpene synthesis and the involved key TFs in tea plant remain to be further explored in future.…”
Section: Transcriptional Activation Mediated By Open Acrs During With...mentioning
confidence: 98%
“…In addition, several studies have shown that external application of JA can affect terpenoid synthesis efficiency (Ayala-Zavala et al, 2005;Kim et al, 2006). Similarly, the release of volatile terpenoids was significantly increased by external application of JAs to tea leaves (Jiao et al, 2022). However, this causal linkage between JA and terpene synthesis and the involved key TFs in tea plant remain to be further explored in future.…”
Section: Transcriptional Activation Mediated By Open Acrs During With...mentioning
confidence: 98%
“… 42 In contrast, when caterpillars of the specialist tobacco hornworm, Manduca sexta , attacks N. attenuata plants, the simultaneous activation of JA and ethylene signaling pathways results in the attenuation of insecticidal nicotine production, indicating an antagonistic interaction of jasmonate and ethyl signaling. 43 These seemingly opposing outcomes of the crosstalk between the JA and ethylene endogenous signaling suggest that the interaction between two different signaling pathways can be realized at different points in the induction process (from the perception of an environmental cue to the expression of resistance mediating metabolism) and that this can be mediated by differential activation of phytohormone-regulated promoters. It also serves to highlight the point that crosstalk between phytohormonal signaling pathways and their differential outcomes can be evolutionarily adapted and behaviorally adjusted to fine-tune plant metabolism to meet the challenges of the current environmental contexts.…”
Section: Context Dependency Of Plant Endogenous Signaling Pathway Cro...mentioning
confidence: 99%
“…Additionally, exogenous application of JA enhanced the resistance of tea plants to E. grisescens by activating defense characteristics, including defense gene expression and the accumulation of defensive proteins and metabolites. For instance, pretreatment with MeJA increased PPO activity by activating the transcripts of CsPPO2 and CsPPO4 [ 40 ] and induced the biosynthesis of defensive catechins and volatiles [ 38 , 42 ]. In the tea diseases, C. camelliae infection significantly increased JA and OPDA content, and E. vexans infection increased the endogenous levels of JA and SA as well as the expression of synthesis-related genes [ 43 , 44 ] ( Table 1 ).…”
Section: The Phytohormones Involved In Pest/pathogen-induced Defense ...mentioning
confidence: 99%